2015
DOI: 10.1093/dnares/dsv021
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of tandem repeats inTribolium castaneumgenome reveals abundant and highly dynamic tandem repeat families with satellite DNA features in euchromatic chromosomal arms

Abstract: Although satellite DNAs are well-explored components of heterochromatin and centromeres, little is known about emergence, dispersal and possible impact of comparably structured tandem repeats (TRs) on the genome-wide scale. Our bioinformatics analysis of assembled Tribolium castaneum genome disclosed significant contribution of TRs in euchromatic chromosomal arms and clear predominance of satellite DNA-typical 170 bp monomers in arrays of ≥5 repeats. By applying different experimental approaches, we revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
89
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(111 citation statements)
references
References 65 publications
8
89
1
Order By: Relevance
“…infestans [36]. SatDNA characterization by genome sequencing suggests that their presence on the euchromatic regions is not uncommon, as has been reported in some insect species as Tribolium castaneum [37] and Locusta migratoria [16], as well as in plant species [38]. For these satDNA families it is probable that classical techniques for satDNA isolation fail due to their lower amount in comparison with the families located in the heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…infestans [36]. SatDNA characterization by genome sequencing suggests that their presence on the euchromatic regions is not uncommon, as has been reported in some insect species as Tribolium castaneum [37] and Locusta migratoria [16], as well as in plant species [38]. For these satDNA families it is probable that classical techniques for satDNA isolation fail due to their lower amount in comparison with the families located in the heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental approach has evident limitations, and can be easily biased, for example, due to the construction of genomic library and the library size. On the other hand, limitations in sequence assemblies regularly make large satDNA domains excluded from datasets, and, as a consequence, short arrays such as those of Cg170 satDNA may become apparently “enriched” in the assembled genome (for the discussion about this point, see [19]). Sets explored in this survey are of comparable size and represent a kind of genomic cross-section that can be indicative of at least some patterns of associations between satDNAs and other genomic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to localized organization into long homogeneous arrays of heterochromatin, growing evidence suggests a much broader, genome-wide distribution of satDNAs [10, 18, 19]. Analysis of sequence variability performed on the 1.688 satDNA of Drosophila [20] and on satDNAs of the beetle Tribolium castaneum [19] showed that satDNA copies located in euchromatic chromosomal domains evolve under similar rules as their counterparts in heterochromatic compartments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations